Ovarian Torsion at 8 weeks of Gestation in a Woman with Threatened Abortion After Frozen-Thawed Embryo Transfer: A Case Report - Ju W; Zhang J; Wang Y; Pan K; Zhang Q; Zhao S; Lian F (Dove Medical Press, 2024)
Wenhan Ju,1 Jinfu Zhang,1,2 Yue Wang,3 Keying Pan,3 Qianwen Zhang,3 Shuai Zhao,3 Fang Lian4 1Guanghua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Shenzhen Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shenzhen, People's Republic of China; 3Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 4Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of ChinaCorrespondence: Shuai Zhao, Shandong University of Traditional Chinese Medicine, No. 16369 Jingshi Road, Jinan, People's Republic of China, Email xiao-xue0531@163.com Fang Lian, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, No. 42 Wenhua West Road, Jinan, People's Republic of China, Email lianfangbangong@163.comIntroduction: Ovarian torsion during pregnancy is a rare condition that requires prompt diagnosis and repositioning to preserve ovarian function.Case Report: A 32-year-old woman underwent a successful pregnancy after FET, but was hospitalized for observation because of a threatened abortion. During the 8th week of pregnancy, a transvaginal ultrasound examination was performed due to sudden lower abdominal pain, which displayed an 8.3× 5.2cm right ovary and a 4.3× 3.6 cm enhanced echogenic mass over the right ovary with striated structures. Consequently, a preliminary diagnosis of ovarian torsion was made, and urgent laparoscopic exploration was conducted. Intraoperatively, the right fallopian tube and right ovary were rotated counterclockwise by 720 degrees. After rotate and reposition the right ovary and fallopian tube, a 3 cm diameter cyst was punctured. After 1 hour of observation, a 2× 1× 1cm segment of ovarian tissue was excised. Pregnancy was maintained with aggressive postoperative luteal support and anti-infective treatment.Conclusion: The use of clomiphene citrate during endometrium preparation for frozen-thawed embryo transfer cycles may elevate the risk of ovarian torsion. Laparoscopic ovarian repositioning after ovarian torsion in pregnant women, even those with threatened abortion, is safe when combined with postoperative anti-infective treatment and intensive luteal support.Keywords: ovarian torsion, frozen-thawed embryo transfer, pregnancy, laparoscopy